2009
DOI: 10.1590/s0103-97332009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Specific induced activity profile at the rotary specimen rack of IPR-R1 TRIGA reactor

Abstract: The IPR-R1 TRIGA nuclear reactor at Nuclear Technology Development Center, CDTN/CNEN, Belo Horizonte, Brazil, has a rotary specimen rack, RSR, outside the reactor core, and it is composed for forty irradiation channels in a cylindrical geometry. The aim of this work is to evaluate the neutron fluence rate distribution at the RSR and its variation under different irradiation conditions by means of specific induced activity measurements. Al-0.1 % Au reference materials were irradiated simultaneously at 100 kW in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Previous work [3] had revealed that the specific induced activity of samples in the RSR has a fluctuation of approximately 2% for samples irradiated on different dates. In order to check variations of thermal and epithermal neutron fluence rates, bare and Cadmium-covered probes were irradiated in the selected irradiation channels on different dates.…”
Section: Rotary Specimen Rackmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work [3] had revealed that the specific induced activity of samples in the RSR has a fluctuation of approximately 2% for samples irradiated on different dates. In order to check variations of thermal and epithermal neutron fluence rates, bare and Cadmium-covered probes were irradiated in the selected irradiation channels on different dates.…”
Section: Rotary Specimen Rackmentioning
confidence: 99%
“…The current core configuration, from 2001, permits operations at a maximum steady-state power of 250 kW [2]. Our previous work [3] on the present core configuration evaluated the specific induced activity profile at the RSR and its variation under different irradiation conditions. For the actual core configuration, there are few experimental works concerning the characterization of the thermal and epithermal neutron fluence rates in IPR-R1 irradiation facilities.…”
Section: Introductionmentioning
confidence: 99%